Direct peroral cholangioscopy with red dichromatic imaging 3 detected the perihilar margin of superficial papillary extension in a patient with intraductal papillary neoplasm of the bile duct. Issue 1 (27th March 2023) - Koiwai, Akinobu; Hirota, Morihisa; Murakami, Keigo; Katayama, Tomofumi; Kin, Ryo; Endo, Katsuya; Kogure, Takayuki; Takasu, Atsuko; Sakurai, Hiroto; Kondo, Noriko; Takami, Kazuhiro; Yamamoto, Kuniharu; et al.
Abstract: Intraductal papillary neoplasms of the bile duct (IPNB) are a tumor derived from bile duct epithelium that tends to spread laterally and non‐invasively. Surgery is the first‐choice treatment for IPNB. It is extremely important to accurately diagnose the extent of lateral tumor extension. Although peroral cholangioscopy (POCS) is a potentially useful modality for detecting tumor range with direct observation, poor image quality is a limitation of POCS. Recently, a new‐generation endoscopy system (EVIS X1) was equipped with functions such as red dichromatic imaging to improve image quality. A 75‐year‐old man with cholangitis was referred to our department. Various imaging studies showed a mass in the middle to lower bile duct and dilatation of the common bile duct and the intrahepatic bile duct. Endoscopic retrograde cholangiopancreatography was performed. A biopsy of the main tumor in the lower common bile duct revealed IPNB. It was difficult to determine the extent of superficial tumor extension with modalities such as contrast‐enhanced computed tomography, magnetic resonance imaging, and endoscopic ultrasonography but the detailed evaluation was possible using POCS with red dichromatic imaging 3. The patient underwent hepatopancreatoduodenectomy. This case suggests the usefulness of direct observation using POCS with red dichromatic imaging 3 to determine the range of IPNB.